The human testes: Estrogen and ageing outlooks - Aatif Hussain; Jacques Gilloteaux (Elsevier, 2020)
This survey highlights some of the fine structures and functions associated with estrogen in the human testes, ageing and contraception. Clarifications obtained with knockout mice models as well as some clinical investigations showed that estrogen receptors significantly influenced the overall maintenance of the testis functions through aromatase activity, intervening in the testosterone production by the Leydig cells and, indirectly with the Sertoli cells. Other autocrine, paracrine and endocrine fading activities of the seminiferous tubule's interstitium, including vascular supply, curtail the maturation of the male gametes while maintaining the blood-testis barrier in ageing. Do Reinke, Charcot-Böttcher and Lubarsch crystalloids, biopsy markers of specific testis cells, resulted of normal or altered functions and/or accumulated deposits out of ageing? The hypothalamo-pituitary-testis axis and feed-back homeostasis (with pineal influence?) regulating the reproductive tissues and phenotype characteristics, can be progressively changed according to individual health history, encompassing life time accumulated environmental toxicants, pharmaceuticals, and age-reduced cardiovascular fitness. The monitoring of all those long-term effects is needed to be better understood to provide future human public health in the care for the old adult, aging population.